Joining of γ-TiAl alloy to Ni-Based superalloy using Ag-Cu sputtered coated Ti brazing filler foil - Simões, Sónia (2018)
Joining γ-TiAl alloy to Ni-based superalloy Hastelloy using Ag-Cu sputtered coated Ti foil as brazing filler was investigated in this study. Brazing experiments were performed at 900, 950, and 980 °C with a dwelling stage of 10 min in vacuum. The microstructure and the chemical composition of the resulting interfaces were analyzed by scanning electron microscopy (SEM) and by energy dispersive X-ray spectroscopy (EDS), respectively. Sound joints were produced after brazing at 980 °C, presenting a multilayered interface, consisting mainly of Ti-Al and Ti-Ni-Al intermetallics close to the γ-TiAl alloy, and of Ti-rich, Ti-Ni, and Cr-Ni-Mo rich phases near Hastelloy. The hardness of the interface, ranging from around 300 to 1100 HV0.01, is higher than both base materials, but no segregation of either Ag solid solution or coarse intermetallic particles was observed. Therefore, the developed brazing filler also avoids the need to perform post-brazing heat treatments that aim to eliminate detrimental extensive segregation of either soft phases or of hard and brittle compounds.